School-Mountain: dismantling power from above - Canaza-Choque, Franklin Américo (2022)
Between the harsh seasons and inclement weather, forgotten and devoid of teachers, transportation, modern infrastructure and educational materials, reaching the field-schools of the mountains can take hours of steep walking for primary school children and small infants, in which the difficulties of rural areas and the hardness of the height may not be the greatest challenge of all. Well, without any privilege, crossing hills and mountains, they are boys and girls who come out of nowhere to conquer everything. From this premise, the study proposes to enlarge the relationship between School-Mountain (MS) in order to forge not only a renewed notion or real line that allows responding to the current dilemmas and challenges of the time, but also allows finding some action engines cast and forged from the heart of the mountain, one that has the ability and spirit to slay the killer. In this way, in line with studies that propose beheading the emperor or provoking an atypical telluric event in the regions of power, this study deposits its soul and spirit within works parameterized by documentary research within the framework of the norms pre-established by the PRISMA methodology. From the results it can be stated that, in that place of glaciers and snow-capped mountains destined to disappear over the years, the high-altitude inhabitants not only lack multiple attentions, but in addition to being out in the open, their cumbersome and brutal onslaught has the impact of strong misadventures, where the school, like never before governs its own challenges.